Analysis And Design Of Enterprise Architecture Using Togaf Adm Framework In Procurement Division And Material Management Division Pt. Inti (persero) - Dian Suci Astuti; Yuli Adam Prasetyo; Rahmat Mulyana (eProceedings of Engineering, 2016)
Implementation of a system in a company provide a significant benefits to align a business activity in the company. A company system is also closely related to the development of information technology. The benefits from the relationship between system and information technology are they can align the relationship between technology and business processes within a company. Enterprise Architecture (EA) is an effective approach, because it has a good structure for system requirements that can be used to design and develop a complex system become a simple system. This research was carried out to build a solution on Enterprise Architecture that can serve as guidelines for achieving the strategic objectives of the company. This architectural solution can be used as a basic sample for manufacture company like PT INTI in the development of Enterprise Architecture, especially in the function of Procurement and Materials Management. Keywords: Enterprise Architecture, Procurement, Material Management